Nano-curcumin enhances the sensitivity of tamoxifen-resistant breast cancer cells via the Cyclin D1-DILA1 axis and the PI3K/AKT/mTOR pathway downregulation - Taraneh Givi; Fatemeh Mohajerani; Zahra Moazezi Tehrankhah; Mohammadjavad Karimi Taheri; Maryam Amirahmadi; Sadegh Babashah; Majid Sadeghizadeh (PLoS ONE, 2025)
This research investigates the effects of nano-curcumin on the expression of Cyclin D1 and DILA1 genes, as well as on the PI3K/AKT/mTOR pathway, in tamoxifen-sensitive and resistant MCF-7 breast cancer cell lines. The IC50 values were determined using the MTT assay. To establish tamoxifen-resistant MCF7 cells, a stepwise exposure to tamoxifen was conducted, gradually increasing the concentration to twice the IC50 dose. Following treatment with nano-curcumin, cell migration, proliferation, and apoptosis were evaluated using a wound healing assay and flow cytometry. Additionally, the impact of nano-curcumin on the PI3K/AKT/mTOR and Cyclin D1 signaling pathways was analyzed via qRT-PCR and Western blot. Nano-curcumin treatment significantly inhibits cell proliferation, viability, and migration and promotes apoptosis in tamoxifen-sensitive and resistant MCF7 cell lines. qRT-PCR and Western blot analyses revealed reduced expression of Cyclin D1, DILA1, NF- κ B, PI3K, AKT, mTOR, VEGF α, MMP2 , and BCL2 , along with increased levels of PTEN, TIMP3, RECK , and BAX . Our results indicate that nano-curcumin mitigates drug resistance by decreasing DILA1 expression, which destabilizes Cyclin D1 protein and downregulates PI3K/AKT/mTOR pathway genes. Additionally, nano-curcumin induces apoptosis and inhibits migration. These findings suggest the nano-curcumin and tamoxifen combination may be a promising therapeutic strategy to overcome drug resistance in ER+ breast malignancies.